Changes of nutritional composition of tempeh during fermentation with the addition of Saccharomyces cerevisiae - SAMSUL RIZAL; MARIA ERNA KUSTYAWATI; A. S. SUHARYONO; VIRDA AULIA SUYARTO (Society for Indonesian Biodiversity, 2022)
Abstract. Rizal S, Kustyawati ME, Suharyono AS, Suyarto VA. 2022. Changes of nutritional composition of tempeh during fermentation with the addition of Saccharomyces cerevisiae. Biodiversitas 23: 1553-1559. This study aimed to determine the effect of the addition of Saccharomyces cerevisiae on changes in nutritional composition during tempeh fermentation. The study used a Completely Randomized Block Design with two treatments and two replications. The first treatment was the type of tempeh inoculum with 4 levels, namely 0.2% commercial inoculum (Raprima), 1% Rhizopus oligosporus inoculum, 1% S. cerevisiae inoculum, and a mixture of 1% R. oligosporus inoculum, and 1% S. cerevisiae inoculum. The second treatment was the length of fermentation with 4 levels, namely 0 hours, 15 hours, 30 hours, and 45 hours. Observation parameters include fat, protein, ash, moisture, carbohydrates, and ?-glucan content during fermentation of tempeh. The data obtained were analyzed statistically using the Barlett and Tukey test then continued with the ANOVA test and the Orthogonal Polynomial-Orthogonal Comparison (OP-OC) test at the 5% level. The results showed that the addition of S. cerevisiae as an inoculum in making tempeh had an effect on changes in nutritional content during tempeh fermentation. The fat content, ash content, and moisture content of tempeh increased during fermentation, while the fat content and carbohydrate content decreased. The addition of 1% S. cerevisiae to tempeh fermentation by 1% R. oligosporus at 45 hours of fermentation resulted in the best nutritional content of tempeh with 17.40% protein content, 8.23% fat content, 65.74% moisture content, 1.33 ash content, 7.30% carbohydrate content, and 0.13% ?-glucan content.